(untitled) (Desarrollo, Estado y Espacio, 2022)
These preliminary notes propose to conceptualize around the scales of neoliberalization, considering the rationalities deployed “from below”, that is, proposing to observe subaltern subjects in their character producer/ reproducer of rationalities, depasivizing the perspectives around these. In this framework, the research seeks to promote a discussion about the difficulties observed in the dimensions that guide the political economy of the scales to explain neoliberal rationalities beyond the domain of the state-national, rationalities that nest in the economic subsystems. In this intersection between state policies and neoliberalization processes vis-à-vis the transformations in the scales of neoliberalization, central questions arise that mark the course of these notes, with what analytical tools to investigate processes of neoliberalization in Latin American contexts? How to contribute to the construction of a multi-scalar approach to address “really existing neoliberalism” in the periphery considering, at the same time, the rationalities deployed “from below” and “from above”? The research uses a multi-scalar approach, which is fundamentally based on secondary sources of information (academic literature) and arises from conceptual discussions maintained for a term of three years in the institutional framework of Centro de Estudios Urbanos y Regionales, mainly in the Group of Desarrollo Regional y Economía Social.